Animals exhibit consistent individual differences in their movement: a case study on location trajectories of Japanese macaques - Takashi Morita; Aru Toyoda; Seitaro Aisu; Akihisa Kaneko; Naoko Hashimoto; Ikki Matsuda; Hiroki Koda (2020)
Researching individual recognition (IR) is essential to understand the life history and adaptive behavior of social animals. Investigation of possible IR clues may also help us build new hypotheses about how social animals distinguish between different individuals. This study investigates behavioral individuality in Japanese macaques (Macaca fuscata), focusing on one specific trait that is movement. Using a recently developed tracking system based on Bluetooth® Low Energy beacons, we collected three-dimensional (3D) location data from five Japanese macaques living in a group cage. A non-parametric, neural network-based analysis of the data revealed the existence of consistent individual differences in extremely limited aspects of the movement data (2-min trajectory of 3D location). Our results support the validity of multimodal approaches in studying IR, beyond the typical single-frame face recognition method, both for researchers and animal agents.